Studi Analisis Kesiapan Penguatan Relevansi Lembaga PAUD Sebagai Fase Pondasi Kurikulum Merdeka - Nur Farida; Pamungkas Stiya Mulyani (PAUDIA : Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2023)
AbstractThe success of achieving the independence curriculum is determined by the level of early childhood education. The purpose of this study was to determine the readiness of each element of the PAUD institution in relevance as the foundational phase of the independent curriculum. This study uses a survey method and is supported by a qualitative approach to translate the data from research findings with a sample of 9 (nine) PAUD institutions in Wonosobo District with Cluster Random Sampling selection based on distance from the city center and 9 (nine) Heads of Research Subjects. Institutions/Schools, 18 (Eighteen) Teachers, and 45 (Forty-five) Guardians of Students and Students. The research instruments are: 1) Interview Sheets for Teachers, Heads of Institutions/Schools, Guardians of Students and Students, 2) Questionnaires for Teachers, Heads of Institutions/Schools, and Parents of students. The results of the study show the readiness of each element of the PAUD institution, starting from the school institutions, teachers, parents of students in implementing an independent curriculum that is oriented to the learning outcomes of PAUD according to what is mandated by the government.Keywords: Readiness; early childhood institution; "freedom" curriculum AbstrakKeberhasilan terwujudnya capaian kurikulum merdeka ditentukan dari tingkat pendidikan anak usia dini. Tujuan penelitian ini adalah mengetahui kesiapan tiap elemen lembaga PAUD dalam relevansi sebagai fase pondasi kurikulum merdeka. Penelitian ini menggunakan metode survey serta di dukung dengan pendekatan kualitatif untuk menerjemahkan data-data hasil temuan penelitian dengan sampel penelitian 9 (Sembilan) Lembaga PAUD di Kabupaten Wonosobo dengan pemilihannya secara Cluster Random Sampling berdasar jarak dari pusat kota dan Subjek penelitiannya 9 (Sembilan) Kepala Lembaga/Sekolah, 18 (Delapan Belas) Guru, dan 45 (Empat Puluh Lima) Wali Murid dan Murid. Instumen penelitiannya adalah: 1) Lembar Wawancara untuk Guru, Kepala Lembaga/Sekolah, Wali Murid dan Siswa, 2) Angket untuk Guru, Kepala Lembaga/Sekolah, dan Orang Tua siswa. Hasil penelitian menunjukan adanya kesiapan setiap elemen lembaga PAUD, mulai dari Pihak Lembaga sekolah, guru, wali murid dalam menerapkan kurikulum merdeka yang berorientasi pada capaian pembelajaran PAUD sesuai yang diamanatkan oleh pemerintah.Kata kunci: Kesiapan; Lembaga PAUD; Kurikulum Merdeka